2020
DOI: 10.1002/er.5422
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion characteristics and fuel cell performance of a cost‐effective high Mn–Low Ni austenitic stainless steel as an alternative to SS 316L bipolar plate

Abstract: Summary In this study, newly developed high manganese (Mn) and low nickel (Ni) austenitic stainless steels were investigated as an alternative to conventionally used SS 316L for bipolar plate applications in proton exchange membrane fuel cells. Systematic studies on the corrosion behavior were carried out in simulated hydrogen and oxygen environments, for both half‐ and fuel‐cell conditions. The Mn‐based SS revealed nobler corrosion potential and comparable passive current densities to that of SS 316L. The pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…The potentiostat tests additionally showed that there is less corrosion in a simulated anode environment and were credited to the decrease in the H+ particles bringing about a negative current that provided cathodic protection to the 316L stainless steel. Recently, Kumar et al 20 studied the behaviors of two grades of stainless steel for BPP application. The magnesium-based stainless steel displayed more passive current density and better corrosion potential compared to nickel-based stainless steel.…”
Section: Stainless Steel As Bipolar Plates Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentiostat tests additionally showed that there is less corrosion in a simulated anode environment and were credited to the decrease in the H+ particles bringing about a negative current that provided cathodic protection to the 316L stainless steel. Recently, Kumar et al 20 studied the behaviors of two grades of stainless steel for BPP application. The magnesium-based stainless steel displayed more passive current density and better corrosion potential compared to nickel-based stainless steel.…”
Section: Stainless Steel As Bipolar Plates Materialsmentioning
confidence: 99%
“…3,18,19 The corrosion resistance of the BPP also can be enhanced utilizing the electrochemical properties of graphene in coating the substrate material and has been investigated by authors. 18,20 Pu et al 18 deposited graphene on the BPP substrate to improve the performance through the provision of the anticorrosion graphene coating for the PEMFC environment. Chung et al 21 developed a graphene layer on a nickel/stainless steel surface, and during this interaction, the carbon molecules at first formed round carbon structures on the nickel grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The passive current density of the modified steel was < 1 μA/cm 2 ; however, the ICR values of both Mn SS (~234.6 mΩ cm 2 ) and 316 L SS (155 mΩ cm 2 at 1.4 MPa) do not satisfy the DoE limit, emphasizing the need of a conductive coating or oxide conductivity enhancement. [40] These works indicate that even though the SS is comparatively safer at normal operating conditions of PEMC, extreme conditions, such as high temperature and potential, could lead to corrosion, necessitating a proper conducting surface coating for long-term durability as discussed in the Section 2.1.1.1.…”
Section: Stainless Steelsmentioning
confidence: 99%
“…The proton exchange membrane fuel cell (PEMFC) is considered to be one of the most prized potential energy conversion devices in the 21st century due to its unique advantages, such as its high rate of energy conversion, pollution-free emissions, and noisefree operation [1][2][3]; however, owing to the high preparation cost of PEMFCs, its application is limited [4]. Bipolar plates (BPs) are key components of PEMFCs, and they are responsible for energy conduction, material transportation, structural support, etc.…”
Section: Introductionmentioning
confidence: 99%